Can cities bounce back better from COVID-19? Reflections from emerging post-pandemic recovery plans and trade-offs - Wahba, Sameh N (SAGE, 2022)
As cities plan for post-COVID recovery, many questions preoccupy mayors, policymakers, planners, and developers. This article examines COVID-19’s impact on cities, drawing on local governments’ developing policies and responses to identify some of the emerging trends and trade-offs. Overall, city recovery will likely involve some transformation to land uses and real estate markets, with increasing demand for urban amenities and nature, and with policies in support of affordable housing, slum upgrading and informal sector employment, to achieve more liveable and inclusive cities. This in turn will depend on the policies, planning, finance, digital infrastructure, and governance systems in place. While many city challenges predate COVID-19, they were exacerbated by the pandemic. The extent to which cities, and especially cities in the global South, will overcome such challenges will depend on political will and the implementation of targeted policies and low-cost investments in sustainability, liveability and inclusion.